2014
DOI: 10.1111/eea.12201
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the experimental setup in research on attractiveness of odours in moths: an example with Busseola fusca

Abstract: Wind tunnel and Y‐tube olfactometer studies are useful for demonstrating the responsiveness of male moths to sex pheromones. However, in the cereal stem borer, Busseola fusca (Fuller) (Lepidoptera: Noctuidae), wind tunnel bioassays yielded poor results when the behavioural responses of females to plant odours were tested. We demonstrated that for B. fusca females, the Y‐tube olfactometer was better suited for measuring the attractiveness of plant odours, compared with the wind tunnel. In particular, we showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Dean & Moraes () concluded from their study that the different rates of volatile emission by Bt and non‐Bt plants could be attributed to the differences in feeding behaviour of Helicoverpa zea (Boddie) larvae on the two treatments, and not due to genetic differences between plants. Other studies have also shown that B. fusca females rely more on physical stimuli than volatile stimuli when selecting a host plant (Calatayud et al, , ), displaying the same orientation towards host and non‐host plants in wind tunnel tests. Busseola fusca females will also oviposit on artificial stems (with no chemostimuli) in no‐choice tests (Khan & Saxena, ), suggesting that plant‐chemical stimuli are not essential in the process of selecting a host plant for oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…Dean & Moraes () concluded from their study that the different rates of volatile emission by Bt and non‐Bt plants could be attributed to the differences in feeding behaviour of Helicoverpa zea (Boddie) larvae on the two treatments, and not due to genetic differences between plants. Other studies have also shown that B. fusca females rely more on physical stimuli than volatile stimuli when selecting a host plant (Calatayud et al, , ), displaying the same orientation towards host and non‐host plants in wind tunnel tests. Busseola fusca females will also oviposit on artificial stems (with no chemostimuli) in no‐choice tests (Khan & Saxena, ), suggesting that plant‐chemical stimuli are not essential in the process of selecting a host plant for oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…The behaviour of 3 rd instar larvae from CCc, VVv, CVv, VVc and CVc ( Fig 1 ; the last letter is in lower case because the insects were reared only up to the 3 rd instar on the control diet [c] or diet enriched with vanillin [v]) were analyzed after 5h of starvation. A Y-tube olfactometer, described by Ngi-Song et al [ 27 ], which has been shown to be useful for demonstrating differences in attractiveness to odours in moths [ 28 ], was used (length of stem: 18 cm; length of each arm: 34 cm; diameter: 4 cm). The closed ends of each chamber were connected with tubing to each arm of the Y-tube.…”
Section: Methodsmentioning
confidence: 99%
“…Responses of C. partellus to plant produced volatiles and authentic standards were tested in a two-arm glass olfactometer as described in Calatayud et al (2014). The Y-tube olfactometer had 2.4 cm internal diameter, 3.2 cm external diameter, 20 cm long arm length and 17 cm short arms' length, it had a 75°angle at the Y-junction.…”
Section: The Y-tube Ofactometer Bioassay (Two-choice Test)mentioning
confidence: 99%